Tra region of the natural conjugative Escherichia coli plasmid pRK100 is F-like - Starčič Erjavec, Marjanca (Acta biologica slovenica, 2002)
The aim of the presented study was to identify the similarity of the pRK100 tra region with tra regions of other conjugative plasmids of Enterobacteriaceae. For this purpose several tra genes were amplified wikh PCRand the nucleotide sequences of the obtained PCR products were determined. The pRK100 is nucleotide sequences were compared to the nucleotide sequences deposited in GenBank and the nucleotide divergence between them was calculated. The obtained results clearly demonstrated, that the tra region of pRK100 is the most similar to the tra region of plasmid F.
Keywords: bakterije; Base Sequence; Baze, zaporedje; Escherichia Coli; F Factor; F faktor; Genetics; geni; molekularna genetika; Plasmids; Plazmidi; Polimerazna, verižna reakcija; Polymerase Chain Reaction